Oxidation of low-density lipoprotein by Cu 2+ and lipoxygenase: an electron spin resonance study - Kalyanaraman, B.; Antholine, William E.; Parthasarathy, Sampath (Biochimica et biophysica acta. General subjects, 1990)
The aim of this work was to obtain spectroscopic evidence for free radicals formed during copper ion- and lipoxygenase-catalyzed oxidation of the low-density lipoprotein. During the initial oxidation phase, a free-radical metabolite derived from the endogeneous α-tocopherol present in the low-density lipoprotein was detected by the electron spin resonance technique. The divalent copper ions were bound to the residual EDTA present in the low-density lipoprotein and to the protein. Production of the α-tocopherol radical was suppressed in the presence of spin traps. Evidence for the low-density lipoprotein-lipid derived radicals was obtained by ESR-spin trapping methods. Implications of these findings in the oxidative modification of the low-density lipoprotein are discussed.